Cylindrical wave diffraction by an absorbing strip - ASGHAR, S.; HAYAT, Tasawar (Archives of Acoustics, 1998)
A solution for the problem of diffraction of a cylindrical sound wave near an absorbing strip introducing the Kutta–Joukowski condition is obtained. The two faces of the strip have impedance boundary conditions. The problem which is solved is a mathematical model for a noise barrier whose surface is treated with acoustically absorbing materials. It is found that the field produced by the Kutta–Joukowski condition will be substantially in excess of that in its absence when the source is near the edge.